Coronary stenting using a 6 French diagnostic catheter: A case report - Dubey, Laxman; Guruprasad, Sogunuru; Subramanyama, Gangapatnam (Journal of Advances in Internal Medicine, 2013)
Guiding catheters have larger lumen diameter as compared to the same size diagnostic catheters, and thus provide adequate arterial blood flow and good visualization of the artery during percutaneous coronary intervention. However, feasibility of percutaneous coronary intervention via diagnostic catheters has been demonstrated in a few studies. This case reports the use of a 6 French diagnostic catheter for both the coronary angiography as well as coronary stenting in a 52-year-old male patient with critical mid left anterior descending artery stenosis on December, 2012. DOI: http://dx.doi.org/10.3126/jaim.v2i2.8781 Journal of Advances in Internal Medicine 2013;02(02):71-73